Addressing scalable, optimal, and secure communications over LoRa networks: Challenges and research directions. Issue 4 (28th June 2018) - Accettura, Nicola; Alata, Eric; Berthou, Pascal; Dragomirescu, Daniela; Monteil, Thierry
Abstract : The Internet of things (IoT) enables large‐scale deployments of very low‐power devices connected through wireless lossy links and able to interact with the surrounding environment (sensing and actuation). Two main challenges are then present: make them communicate; handle their energy consumption while respecting some cost constraints. Low‐power wide area networks (LPWANs) tackle these challenges by offering long‐distance coverage while guaranteeing the use of a very little amount of energy for communications. Among many LPWAN technologies, long range (LoRa) networks provide a very promising but incomplete basis for satisfying the needs expressed by the applications running on low‐power devices. This paper describes the LoRa technology from the architectural point of view and points out those aspects that permit its seamless integration into the IoT. As major contribution, a focus on the current and future research on LoRa networks is provided by inspecting 3 facets: scalability, quality of service, and security.